New insights into human lysine degradation pathways with relevance to pyridoxine‐dependent epilepsy due to antiquitin deficiency. Issue 4 (15th April 2019) - Crowther, Lisa M.; Mathis, Déborah; Poms, Martin; Plecko, Barbara
Abstract: Deficiency of antiquitin (ATQ), an enzyme involved in lysine degradation, is the major cause of vitamin B6 ‐dependent epilepsy. Accumulation of the potentially neurotoxic α‐aminoadipic semialdehyde (AASA) may contribute to frequently associated developmental delay. AASA is formed by α‐aminoadipic semialdehyde synthase (AASS) via the saccharopine pathway of lysine degradation, or, as has been postulated, by the pipecolic acid (PA) pathway, and then converted to α‐aminoadipic acid by ATQ. The PA pathway has been considered to be the predominant pathway of lysine degradation in mammalian brain; however, this was refuted by recent studies in mouse. Consequently, inhibition of AASS was proposed as a potential new treatment option for ATQ deficiency. It is therefore of utmost importance to determine whether the saccharopine pathway is also predominant in human brain cells. The route of lysine degradation was analyzed by isotopic tracing studies in cultured human astrocytes, ReNcell CX human neuronal progenitor cells and human fibroblasts, and expression of enzymes of the two lysine degradation pathways was determined by Western blot. Lysine degradation was only detected through the saccharopine pathway in all cell types studied. The enrichment of 15 N‐glutamate as a side product of AASA formation through AASS furthermore demonstrated activity of the saccharopine pathway. We provide first evidence that the saccharopine pathway is the major route of lysine degradation in cultured human brain cells. These results support inhibition of the saccharopine pathway as a new treatment option for ATQ deficiency.